A Holistic View of Corporate Sustainability: From Disclosure to Governance Development - Tri Cahya, Bayu; Fitri Habsari, Rika; Harjito, Yunus; Paramita Sari, Ratih; Ali, Nor Aishah Mohd (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2025)
This study examines the effects of carbon emission disclosure, green accounting, material flow cost accounting, and the presence of women on boards of directors on sustainability development. Sustainability development emphasizes that companies carrying out business do not only focus on economic benefits, but also on benefits for the surrounding environment. This study utilizes secondary data, specifically annual reports and sustainability reports, obtained from the official websites of the relevant companies. The population used consists of companies that received the Asia Sustainability Report Rating award and were listed on the Sharia Securities List during the 2018-2023 period, totaling 66 companies. The sampling technique employs purposive sampling to collect company data that matches the specified criteria. Data analysis employs classical assumption tests and hypothesis testing using multiple regression analysis, aided by the IBM SPSS program. The results showed that carbon emission disclosure and material flow cost accounting had a significant impact on sustainability development. Green accounting and women’s directors are expected to impact sustainable development, but this has not been proven in this study. The lack of effect of green accounting on sustainable development is due to the companies studied not clearly defining the indicators of green accounting in their financial statements. Information related to social and environmental issues has not been fully disclosed. In addition, some of the companies studied tend to appoint few women as directors, which is suspected to be the reason for the unproven influence of women on the board of directors on sustainability development.